Forchheimer groundwater flow law type curves for leaky aquifers - Birpinar, ME; Sen, Z (ASCE-AMER SOC CIVIL ENGINEERS, 2004)
An analytical solution has been developed for radial Forchheimer groundwater flow toward a fully penetrating well in a leaky aquifer. This equation has a second-order polynomial form which reduces to the classical Darcian flow case when the parameter of the second-order term is equal to zero. The solution methodology is based on the volumetric approach concept. The results are presented as a set of type curves for a leaky aquifer with non-Darcian groundwater flow. They are checked numerically against already existing classical solutions and very good agreement is obtained with less than 1% error. The type curve expressions presented herein are general and reduce to the classical Theis and Hantush Darcian flow solutions. The application of the Forchheimer law type curve is performed for 8-day-long time-drawdown data from Chaj-Doab area in Pakistan.
Keywords: aquifers; leakage; ground-water flow; NONLINEAR RADIAL FLOW; CONFINED AQUIFERS; WELLS; Engineering; Environmental Sciences & Ecology; Water Resources